Nonlinear associations between sleep duration and the risks of all-cause and cardiovascular mortality among the general adult population: a long-term cohort study - Li, Jie; Wu, Qiyong; Fan, Li; Yan, Zining; Shen, Dan; Zhang, Ming (Frontiers in Cardiovascular Medicine, 2023)
Objective: To explore the association between sleep duration and all-cause and cardiovascular mortality in the general population. Methods: This study included 26977 participants aged ≥18 years who were included in the National Health and Nutrition Examination Survey (NHANES) database from 2005 to 2014. For all participants, data regarding cardiovascular and all-cause deaths were collected through December 2019. Sleep duration was estimated using a structured questionnaire, and participants were then divided into 5 groups based on this information (sleep duration ≤5 hours, 6 hours, 7 hours, 8 hours, or ≥9 hours). Kaplan-Meier survival curves were used to assess mortality among the sleep duration groups. Multivariate Cox regression models were used to analyze the relationship between sleep duration and mortality. A restricted cubic spline regression model was then drawn to determine the nonlinear relationship between sleep duration and all-cause and cardiovascular mortality. Result: The mean age of participants was 46.23 ± 18.48 years, and 49.9% of the study subjects were men. During a median follow-up of 9.42 years, 3153 participants died of all-cause deaths; of these, 819 were cardiovascular deaths. The lowest cumulative survival rates for all-cause mortality and cardiovascular mortality were seen in the ≥9 hours and ≤5 hours groups, respectively. When a sleep duration of 7 hours was used as the reference, the hazard ratios (95% confidence intervals) for all-cause mortality were 1.28 (1.14-1.44) for ≤5 hours, 1.10 (0.98-1.23) for 6 hours, 1.21 (1.10-1.34) for 8 hours, and 1.53 (1.35-1.73) for ≥9 hours. The hazard ratios (95% confidence intervals) for cardiovascular mortality were 1.32 (1.04-1.67) for ≤5 hours, 1.22 (0.97-1.53) for 6 hours, 1.29 (1.05-1.59) for 8 hours, and 1.74 (1.37-2.21) for ≥9 hours. The nonlinear relationship between sleep duration and all-cause and cardiovascular mortality was found to be U-shaped, with inflection point thresholds of 7.32 hours and 7.04 hours, respectively. Conclusion: The risk of all-cause and cardiovascular mortality is lowest when sleep duration is approximately 7 hours.